Investigation on noise from shock/isotropic turbulence interaction using direct numerical simulation. (8th December 2020) - Shi, Fangcheng; Gao, Zhenxun; Jiang, Chongwen; Lee, Chun-Hian
Highlights: Turbulence noise is amplified by the shock/turbulence interaction. The normal stresses in transverse directions contribute greatly to the noise. Three mechanisms of noise variation under shock/turbulence interaction are found. Acoustic intensity parts for different turbulence scales are increased under STI. Acoustic intensity increase for interaction of smaller and larger scales is larger. Graphical abstract: Abstract: Direct numerical simulation of shock/isotropic turbulence interaction combining Lighthill's acoustic analogy is conducted to study the influence of shock/turbulence interaction (STI) on the turbulence noise in the farfield. The acoustic statistics are adopted to quantify the influence of STI on the turbulence noise. The results show that STI increases the power spectral density in almost the whole frequency band and obviously amplifies the acoustic intensity. Based on the numerical results and the theoretical analysis, the primary noise sources are identified. The normal Reynolds stress components in the transverse direction contribute greatly to the noise at the observers. By applying the Rankine-Hugoniot relation and the spatial and temporal Fourier analysis on the simplified noise source, the mechanisms of turbulence noise variation under STI are also investigated, which can be divided into three parts. First, the compression effect of the shock wave increases the downstream density. Second, STI increases the value of turbulent kinetic energy spectrum over the entire wavenumber range. Third, the noise sources in the high frequency band are amplified under STI. Additionally, the transverse velocities are filtered in wavenumber space and the influence of STI on turbulence noise is studied from the perspective of the turbulence scales. The contribution of acoustic intensity radiated from "smaller" or "larger" turbulence scales is decreased, and the contribution of acoustic intensity radiated from the interaction of "smaller" and "larger" turbulence scales is increased under STI.